Seismic processed data (Ocean Bottom Seismometer working area dataset, profile P200e) during RRS JAMES COOK cruise JC228, Guatemala Basin, North Pacific Ocean - Ingo Grevemeyer; Timothy J Henstock; Yuhan Li; Anke Dannowski (PANGAEA, 2025)
The data set comprise processed active-source seismic data collected with ocean bottom seismometer (OBS). The seismic shots were recorded in the trench outerrise region of the subduction zone off Costa Rica during the expedition JC228 of the research vessel RRS JAMES COOK in December 2022 and January 2023. The data set consists of 36 OBS stations deployed at an interval of 3.5 to 7 km receiving shots of a tuned 5000 cubi-inch airgun array, fired at 90 s interval. The seismic line is a 250 km long East-West trending profile covering the incoming oceanic plate and the Costa Rican deep sea trench. Each OBS consists of 4 channels (channel 1: hydrophone; channel 2: horizontal component 1; channel 3: horizontal component 2; channel 4: vertical component).